Preconceptions of Bachelor of Science Education (Honours) Degree in Physics Students about Compton Effect - Edson Mudzamiri; Enselem Tashayanyika Madzudzo; Nadaraj Govender (Physics Education Research Journal, 2025)
Physics education research has established that students’ preconceptions play a dominant role in teaching and learning of physics from elementary levels up to University. College students have been known to ignore information presented to them in lectures when it is inconsistent with their prior convictions some which are misconceptions. Research studies show that students’ preconceptions must be identified first before new concepts and explanations are learnt. This study aims to determine preconceptions of Bachelor of Science Education (Honours) Degree in Physics Students around the concept of Compton scattering particularly as explained using the concept of light. This qualitative study was conducted with 40 Bachelor of Science Education (Honours) degrees in Physics students at a state university in Zimbabwe. Data were analyzed descriptively. The students’ preconceptions that emerged were categorized as scientific concepts, misconceptions, lack of concept and error. The results showed that average of 21.8% of students had scientific concepts, 45.76% of students experience misconceptions, 18.54% of students experience lack of concepts and 14.23% of the students experience errors. This study revealed that not all preconceptions held by students are misconceptions as the results show a mixture of correct ant incorrect conceptions about Compton Effect. The study recommends that it is important to identify students’ preconception on Compton Effect to enable instructors to design effective instructional interventions and strategies for reinforcement of correct preconceptions and conceptual change for the wrong preconceived ideas.